2007
DOI: 10.1182/blood.v110.11.428.428
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological (NP) Dysfunction and Neuroimaging Abnormalities in Neurologically Intact Adult Patients with Sickle Cell Disease (SCD).

Abstract: Background. Brain dysfunction may be the most important and least studied problem afflicting the aging SCD population. 25% of neurologically intact pediatric SCD patients have NP dysfunction and silent CNS infarction. In children, age is associated with progressive decline in NP scores suggesting adults are at risk for progressive brain injury and NP decline. Objective. To determine the extent of NP impairment, the prevalence of MRI abnormalities, and their relationship in neurologically asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…5,6 Strokes and SCIs have been linked to cognitive impairment in SCD. However, recent studies have found cognitive dysfunction in children [7][8][9] and adults [10][11][12] even in the absence of MRI-detectable cerebral injury. 7,8,10 Children with SCD typically have lower full-scale IQ scores, poorer academic achievement, and impaired processing speed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 Strokes and SCIs have been linked to cognitive impairment in SCD. However, recent studies have found cognitive dysfunction in children [7][8][9] and adults [10][11][12] even in the absence of MRI-detectable cerebral injury. 7,8,10 Children with SCD typically have lower full-scale IQ scores, poorer academic achievement, and impaired processing speed.…”
Section: Introductionmentioning
confidence: 98%
“…However, recent studies have found cognitive dysfunction in children [7][8][9] and adults [10][11][12] even in the absence of MRI-detectable cerebral injury. 7,8,10 Children with SCD typically have lower full-scale IQ scores, poorer academic achievement, and impaired processing speed. 7,8 Similarly, adults with SCD exhibit impairments in processing speed, working memory, global cognitive function, and executive function.…”
Section: Introductionmentioning
confidence: 98%
“…Further, silent cardiovascular events and chronic hypoxia negatively influence cognitive development resulting in impairments in attention, memory, processing speed, and executive functions that persist in adulthood (Jorgensen et al, 2017; Kirkham & Datta, 2006). Among adults with SCD, 36% score 1 standard deviation and 5% score 2 standard deviations below the population mean in the Processing Speed Index of the Wechsler Adult Intelligence Scale III (Vichinsky et al, 2010). Furthermore, approximately 50% of adults with SCD have silent cerebral infarcts which are associated with cognitive impairments (Kassim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, approximately 50% of adults with SCD have silent cerebral infarcts which are associated with cognitive impairments (Kassim et al, 2016). Abnormalities in the basal ganglia, thalamus, and white matter integrity have been associated with neurocognitive impairments among adults with SCD (Mackin et al, 2014; Vichinsky et al, 2010). While the underlying etiology of neurocognitive impairment varies between stroke and SCD, both groups experience poor outcomes in daily living associated with cognitive impairments (Mole & Demeyere, 2018; Sanger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%